Fast identification of individuals based on iris characteristics for biometric systems - Rogeri, J. G. [UNESP]; Pontes, M. A. [UNESP]; Pereira, A. S. [UNESP]; Marranghello, N. [UNESP]; Araujo, A. F.; Tavares, João Manuel R. S. (My University, 2012)
Nowadays, systems based on biométrie techniques have a wide acceptance in many different areas, due to their levels of safety and accuracy. A biometrie technique that is gaining prominence is the identification of individuals through iris recognition. However, to be proficiently used these systems must process their recognition task as fast as possible. The goal of this work has been the development of an iris recognition method to produce results rapidly, yet without losing the recognition accuracy. The experimental results show that the method is quite promising. © 2012 Taylor & Francis Group.
Keywords: Biometric systems; Identification of individuals; Iris recognition; Recognition accuracy; Image processing; Medical image processing; Biometrics